Association Study Between Thermal Front Phenomena and Bali Sardinella Fishing Areas in Bali Strait - Argo Galih Suhadha; Andi Ibrahim (Indonesian Journal of Geography, 2020)
Thermal front has been widely used as a parameter for determining ﬁshing zones. Tis study aimed to  determine  the  thermal  front  distribution  and  to  analyze  its  association  with  the  Bali  Sardinella  ﬁshing zones  in  the  Bali  Strait.  Termal  front  generated  using  sea  surface  temperature  (SST)  from  Aqua  MODIS imagery. Meanwhile, the ﬁshing point data of Bali Sardinella were collected to validate our analysis results. Te data were analyzed into Spatio-temporal information. Te main facts that stand out are that the thermal front  was  predominantly  found  in  the  peak  of  ﬁrst (April)  and  second  (September)  transitional  season, which was the peak season for the thermal front to occur in a year. Te least of the thermal front occurred in the  South-west  monsoon.  Te  linear  relationship  was found  when  the  peak  of  thermal  front  occurrence compared to the number of catch yields. Based on matching distance analysis, the maximum distance used (twenty  kilometres  buﬀer)  show  36  matching  points from  101  data  compared  or  at  range  35.6%.  In conclusion, there is a linear relationship between the thermal front parameter and catch yield. It is still used to predict the ﬁshing zone, even though the correlation is not signiﬁcantly found.